What if we had a magnetograph at Lagrangian L5?. Issue 11 (10th November 2016) - Pevtsov, Alexei A.; Bertello, Luca; MacNeice, Peter; Petrie, Gordon
Abstract: Synoptic Carrington charts of magnetic field are routinely used as an input for modelings of solar wind and other aspects of space weather forecast. However, these maps are constructed using only the observations from the solar hemisphere facing Earth. The evolution of magnetic flux on the "farside" of the Sun, which may affect the topology of coronal field in the "nearside, " is largely ignored. It is commonly accepted that placing a magnetograph in Lagrangian L5 point would improve the space weather forecast. However, the quantitative estimates of anticipated improvements have been lacking. We use longitudinal magnetograms from the Synoptic Optical Long‐term Investigations of the Sun (SOLIS) to investigate how adding data from L5 point would affect the outcome of two major models used in space weather forecast. Key Points: Data from a magnetograph at Lagrangian L5 point will result in significant differences in forecasted (WSA‐ENLIL) solar wind speed Data from L5 will affect PFSS model outcome in respect to areas of opened field and orientation of large‐scale magnetic field neutral lines